New Configuration of a Three Phase Dynamic Voltage Restorer (DVR) for Voltage Disturbances Mitigation in Electrical Distribution System - OMAR, ROSLI (SPRINGER, 2012)
This paper presents the newtopology of a three-phase four-wireDynamicVoltage restorer (DVR) for mitigating voltage disturbances in low voltage distribution system. The proposed DVR topologies are consist of filtering scheme, isolation or distribution transformer, injection transformer winding and two split DC-link capacitors. The direct-quadrature-zero transformation techniquewas used as a controller of the proposedDVR. The suggested topologies and its controller was verified through simulation usingMATLAB/SIMULINK Sim- Power System Toolbox and implemented in a prototype of the DVR with 5 KVA of the power rating. The experimental and simulation results validate the capability in compensating of voltage disturbances